Розробка системи електронної комерції книгарні - Улан, В. В. (ХНУРЕ, 2025)
This article discusses the creation of an e-commerce system for a bookstore that facilitates the transІТion from traditional paper sales to digІТal solutions. Іt emphasizes how modern technology has changed trading strategies, making e-commerce vital to business growth. Built on a client-server architecture, the system supports three roles: unregistered users, registered users, and administrators with special functions such as browsing, ordering, and managing the system. The study outlines the key stages of development and emphasizes the benefits: improved customer experience, optimized operations, and increased market competitiveness.
Keywords: електронна комерція; книгарня